Conservation of Natural Resources in Infrastructure Development and Climate Action - Practices in the Past and Present Scenario, and Forecast for Future - Shrestha, Diwat Kumar; Praveen, B. M.; Gorkhaly, G.P. (NPRC Journal of Multidisciplinary Research, 2025)
Background: The conservation and utilization of natural resources in infrastructure development are crucial for achieving sustainable growth while addressing climate change challenges. The rapid expansion of infrastructure has often led to environmental degradation, necessitating a shift toward more sustainable practices. Objective: This study aims to examine past practices, assess the current scenario, and propose future strategies for integrating environmental sustainability into infrastructure planning and implementation. Methods: The study reviews historical infrastructure development approaches, analyzes the impact of modern industrialization on natural resources, and evaluates existing sustainable infrastructure initiatives. It also explores policy frameworks, technological advancements, and community-based solutions for fostering climate-resilient infrastructure. Findings: Traditional infrastructure development was resource-efficient and environmentally harmonious but slow. However, rapid urbanization and industrialization, driven by heavy machinery, have led to severe environmental consequences such as deforestation, soil degradation, water depletion, and biodiversity loss. The current scenario highlights an urgent need for climate-resilient and eco-friendly infrastructure as climate change intensifies risks like extreme weather events, rising temperatures, and resource scarcity. Despite progress in adopting green technologies, weak policy enforcement and unsustainable practices persist. Conclusion: A transition toward sustainable infrastructure requires policy reforms, the adoption of eco-friendly construction techniques, the integration of renewable energy, and active community participation. Strengthening environmental regulations, promoting circular economy principles, and leveraging advanced technologies like Artificial Intelligence (AI) and Geographic Information Systems (GIS) can enhance climate-adaptive infrastructure planning. Novelty: This study provides a comprehensive analysis of past and present infrastructure development practices while proposing innovative, technology-driven, and policy-based solutions to enhance sustainability. It underscores the need for a multi-sectoral approach to balance economic growth with environmental conservation.